Bone Substitute Used in Oral Surgery: Comparison of Physicochemical Characteristics of Allografts, Xenograft and Synthetic Materials Compared to Autogenous Bone - Antoine Berberi; Georges Aad (Advanced Concepts in Medicine and Medical Research Vol. 3, 2023)
Objectives: Many bone substitutes have been proposed for bone regeneration, and researchers have focused on the interactions occurring between grafts and host tissue, as the biologic response of host tissue is related to the origin of the biomaterial. Bone substitutes used in oral surgery and implantology include allografts, xenografts and synthetic materials that are frequently used to compensate bone loss or to reinforce repaired bone by encouraging new bone ingrowth into a defect site, but little is currently known about their physicochemical characteristics. The aim of this study was to evaluate a number of physical and chemical properties in a variety of granulated mineral-based biomaterials used in oral surgery and to compare them with those of autogenous bone. Materials and Methods: Autogenous bone and fourteen commercial biomaterials of human, bovine and synthetic origins were studied by high-resolution X-ray diffraction, atomic absorption spectrometry, and laser diffraction to determine their chemical composition, calcium release concentration, crystallinity and granulation size. Results: The highest calcium release concentration was 24. 94 mg/g for Puros® and the lowest one was 1.87 mg/g for OCS-B® compared to 20.15 mg/g for natural bone. The range of particles sizes, in term of median size D50, varied between 6.72 \(μ\)m for Ingenios™ B-TCP and 902.41 \(μ\)m for OsteoSponge®, compared to 282.1 \(μ\)m for natural bone. All samples displayed a similar hexagonal shape as bone, except Ingenios \(β\)-TCP, Macrobone® and OsteoSponge, which showed rhomboid and triclinic shapes, respectively. Conclusion: Commercial bone substitutes significantly differ in terms of calcium concentration, particle size, and crystallinity, which may affect their in-vivo performance.